PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN MEDIA GAMBAR ANIMASI - Fatmawati, Fatmawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this research was to describe the increasing of the student’s ability in writing poetryby using animation image. This research was action research with qualitative and quantitative approach. The result showed that The teacher’s activity in learning of writing poetry using animation image increased from 59% in cycle I to 85% in cycle II. Furthermore, the student writing poetry ability increased in cycle II. Using animation image improved the student’s ability in writing poetry. Kata kunci: menulis, puisi, media, media gambar animasi